The Influence of Accounting Understanding, Utilization of IT, Education Level, Internal Control, and Work Experience on the Quality of Financial Reports of Village Credit Institutions (LPDs) - Putu Kepramareni; Ni Nyoman Santi Dewi; Ida Ayu Nyoman Yuliastuti; Yolanda Patrician Simanjuntak (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2024)
The quality of financial reports is crucial for comparing performance across periods in institutions like the Village Credit Institution (LPD). However, many financial reports have emerged as uninformative and of low quality. This study aims to examine how factors such as job experience, education level, internal control, and accounting knowledge impact the quality of LPD financial reports in Denpasar City. The study population comprised 552 LPD employees involved in preparing financial reports, and through purposive sampling, 102 respondents were selected, including leaders, supervisory bodies, and accounting staff with at least two years of experience. Data were collected via questionnaires and documentation and analyzed using multiple linear regression. The results indicate that while accounting knowledge and internal control do not affect the quality of LPD financial reports, the use of information technology, education level, and work experience positively influence the improvement of financial report quality. These findings highlight the importance of investing in employee education, training, and technology to enhance financial reporting standards at LPDs.